O uso da volatilidade realizada na simulação histórica ajustada para cálculo do VaR - Costa, Fabiola Medina (2010)
This paper proposes the historical simulation model to calculate the VaR, considering return ajusted by the realized volatility measured from intraday returns. The database consists of five most liquid share among the different segments of Bovespa Index. For the proposed methodology we used two of the empirical theories of the empirical literature - adjusted historical simulation and realized volatility. The Kupiec tes and Christoffersen test are used to analized and veryfy the proposed methodology performance.